Cash benefits to disabled persons in Brazil: An analysis of BPC – Continuous Cash Benefit Programme - Marcelo Medeiros Coelho de Souza; Déborah Diniz; Flávia Squinca (Institute for Applied Economic Research (ipea), 2015)
The paper presents an analysis of the Continuous Cash Benefit Programme (BPC, which stands for Benefício de Prestaç\~ao Continuada in Portuguese), an unconditional cash transfer to the elderly or to extremely poor individuals with disabilities. The information used in the assessment stems from the study of court decisions and laws related to the programme since its implementation, an analysis based on questionnaires applied to medical experts, interviews with the programme managers, as well as a review of pre-existing studies regarding BPC. In order to contribute to the management of the programme, as well as to improvements or even implementation of similar programmes in other countries, the study gives some recommendations about the design, operation and future evaluations of the programme.
Keywords: I38; 330; BPC; Disability; Cash Transfers; Cash Benefits; Social Assistance